DISPOSISI MATEMATIS SISWA DITINJAU DARI KEMAMPUAN MENYELESAIKAN MASALAH BERBENTUK OPEN START DI SMP NEGERI 10 PONTIANAK - Maisaroh, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractProblem solving ability is one of the base abilities that should be mastered and improved by students. Besides problem solving ability, math also concerns about affective aspect which is mathematical disposition. The purpose of this research is to description the students’ mathematical dispositions observed from ability in solving open start problems at SMP Negeri 10 Pontianak. The research method used is descriptive and the form of research is survey.the subject of this research were the seventh grade students class A that consist of 38 students. The technique of data collection were measurement technique is problem solving test and mathematical disposition scale. The results in this research shows that students’ mathematical disposistion varies based on the problem solving ability. Students who have the same problem solving ability turn out have different mathematical disposition, that are have mathematical disposition very high, high, and medium level.Keywords : Students’ Mathematical Disposition, Problem Solving Ablity, Open Start Problem